Life-cycle analysis (LCA) to restore community building portfolios by building back better II: Decision formulation. (May 2020) - Wang, Yingjun; Wang, Naiyu; Lin, Peihui; Ellingwood, Bruce; Mahmoud, Hussam
Highlights: A LCA based rebuilding decision methodology is proposed for building portfolios. Community-dependent resilience goals are incorporated in the decision formulation. The methodology is applied in a testbed community and key features are identified. Abstract: The catastrophic social, economic, and political impact from extreme natural hazards in recent years, e.g. Hurricane Katrina (2005), the Christchurch Earthquake (2011), and the Great East Japan Earthquake and Tsunami (2011), have engendered questions from public officials, engineers and planners as to how a community's damaged building portfolio might be best reconstructed to enhance its performance in future hazards. The concept of building back better reflects a reconstruction approach aimed at enabling the community to achieve better performance in future hazard events. Building portfolio life-cycle analysis, developed in a concurrent study, can quantify the impact of specific reconstruction policies and decisions on the building portfolio within a community. This approach, coupled with community-dependent resilience goals aimed at limiting functionality loss and ensuring quick recovery, is utilized in this study to suggest optimal policies for post-disaster reconstruction and to guide cost-effective public decisions aimed at ensuring community resilience. The feasibility of this concept is explored using reconstruction of a mid-size community following a severe earthquake as an example in which key features that may affect optimal reconstruction decisions by community planners are identified.